Psychiatric Disorders, Antiretroviral Medication Adherence and Viremia in a Cohort of Perinatally HIV-Infected Adolescents and Young Adults. Issue 7 (July 2018) - Bucek, Amelia; Leu, Cheng-Shiun; Benson, Stephanie; Warne, Patricia; Abrams, Elaine J.; Elkington, Katherine S.; Dolezal, Curtis; Wiznia, Andrew; Mellins, Claude Ann
Abstract : Background: Perinatally HIV-infected (PHIV+) adolescents and young adults (AYA) are at risk for suboptimal antiretroviral therapy (ART) adherence and mental health and substance use problems that, in HIV-infected adults, predict nonadherence. Studies on the relationship between psychiatric and substance use disorders (SUD) and adherence among PHIV+ AYA are limited, but may be important for informing evidence-based interventions to promote adherence. Methods: Data were analyzed from 3 annual follow-up interviews (FU2–FU4, N = 179) in a longitudinal study of PHIV+ AYA. Psychiatric disorders (anxiety, disruptive behavior, mood and SUD) were assessed with the Diagnostic Interview Schedule for Children. Adherence was self-reported missed ART doses within the past week. Viral load (VL) results were abstracted from medical charts. Multiple logistic regression analyzed cross-sectional associations between psychiatric disorders and (1) missed ART dose and (2) VL > 1000 copies/mL. Multiple linear regression assessed associations between psychiatric disorders and proportion of VL values >1000 copies/mL over time. Results: At FU2, 53% of PHIV+ AYA had any psychiatric disorder, 35% missed an ART dose in the past week and 47% had a VL > 1000 copies/mL. At FU2, behavioral disorders were associated with missed dose ( P = 0.009) and VL > 1000 ( P = 0.019), and mood disorders were associated with missed dose ( P = 0.041). At FU4, behavioral disorders were associated with missed dose ( P = 0.009). Behavioral disorders ( P = 0.041), SUD ( P = 0.016) and any disorder ( P = 0.008) at FU2 were associated with higher proportion of VLs >1000 across FU2–FU4. Conclusions: Addressing psychiatric disorder and SUD among PHIV+ AYA may improve ART adherence outcomes in this population. Targeted interventions should be developed and tested.